Modulation of South Asian Jet Wave Train on the Extreme Winter Precipitation over Southeast China: Comparison between 2015/16 and 2018/19 - Li, Xiuzhen; Wen, Zhiping; Huang, Wan-Ru (Journal of climate, 2020)
Two extremely wet winters in 2015/16 and 2018/19 over Southeast China are compared in this study. South-to-north discrepancies appear in the spatial distribution of precipitation, with anomalous precipitation centered over the southeast coast in 2015/16 and the lower reaches of Yangtze River valley in 2018/19, respectively. Both instances of enhanced precipitation are ascribed mainly to warm and moist advection from the south, with transport in 2015/16 partly by a deepened India–Burma trough to the west, whereas with transport in 2018/19 mainly by a subtropical western North Pacific anticyclone (WNPAC). Both the India–Burma trough and WNPAC are maintained by the wave trains propagating along the South Asian jet, which are zonally offset by a quarter-wavelength. Further study of the wave train sources in 2015/16 and 2018/19 shows that they both tend to originate from extremely strong storm-track activity over the North Atlantic but have different displacement. The former is located more northeastward than the mean storm track and is modulated by a strong positive NAO, whereas the latter lies over the midlatitude central North Atlantic along with a circumglobal teleconnection. These differences further result in a quarter-wavelength offset in the Rossby wave source near the entrance of the South Asian jet by the convergence of upper-level divergent wind.